Review Faktor Pembentuk Perilaku Belajar Siswa Generasi Z Dalam Ruang Kelas - Septian, Nandang; Wibisono, Andriyanto (RESEARCH AND DEVELOPMENT JOURNAL OF EDUCATION, 2021)
Classroom has a significant role in student learning performance. So, its procurement becomes a concern. Nowdays, classrooms have not gained much attention. The preponderances of classroom conditions are old. They exist based on the preferences of prior generations. It is reputed to be less relevant for the current age. Generation Z has different learning behavior from the preceding cohort. From this phenomenon, it is crucial to develop an ideal classroom. Thus, the first step could conduct a study related to user learning behavior in the classroom. It is important to understand their wants and needs. This study reviewed nine previous inquiries related to student learning behavior through systematic literature review method. It provides an overview of student's experiences while learning in the classroom. The study concludes several factors that influenced Generation Z's learning behavior. They are classroom physical elements, self-uplifting, institutions support, and social affection. This result becomes useful information for education principals.Â  Also, the next study can use it as an instrument to test on college students. This selection of college students is the absence of this topic research. It is because previous studies have focused on secondary or higher school students. So, it will enrich research on the factors that influence learning behavior